New fully evolutionary models for asteroseismology of ultra- massive white dwarf stars - Corsico, Alejandro Hugo (2020)
Ultra-massive hydrogen-rich (DA spectral type) white dwarf (WD) stars (M * > 1M ) coming from single-star evolution are expected to harbor cores made of 16 O and 20 Ne, resulting from semi-degeneratecarbon burning when the progenitor star evolves through the super asymptotic giant branch (S-AGB) phase. These stars are expected to be crystallized by the time they reach the ZZ Ceti instability strip (T eff ∼ 12 500 K). Theoretical models predict that crystallization leads to a separation of 16 O and 20 Ne in the core of ultra-massive WDs, which impacts their pulsational properties. This property offers a unique opportunity to study the processes of crystallization. Here, we present the first results of a detailed asteroseismic analysis of the best-studied ultra-massive ZZ Ceti star BPM 37093. As a second step, we plan to repeat this analysis using ultra-massive DA WD models with C/O cores in order to study the possibility of elucidating the core chemical composition of BPM 37093 and shed some light on its possible evolutionary origin. We also plan to extend this kind of analyses to other stars observed from the ground and also from space missions likeKepler and TESS.